Perceptions of police misconduct in Taiwan: does procedural justice matter? - Lai, Yung-Lien (Journal of crime and justice, 2023)
Police misconduct erodes police-citizen relations, which in turn, discourages people from cooperating with police. While a substantial volume of research has focused on how citizens’ demographics, media trust, and neighborhood context can exert an influence on perceptions of police misconduct, very little research has explored the impact of procedural justice in this regard. To fill in the gaps in this literature, the present study utilizes Structural Equation Modeling (SEM) to examine factors affecting citizens’ perceptions of police misconduct in Taiwan. Data were obtained from a CATI telephone survey of 1,806 residents in Metropolitan Taipei in 2014. It was found that citizens’ primary concerns of police misconduct include the covering-up of misconduct on the part of powerful suspects/celebrities, followed by the abuse of power by legal authorities, and the discriminatory enforcement of regulations, respectively. The results revealed importantly that procedural justice, perceptions of crime prevalence, and gender had significant direct influences, whereas media trust, victimization, and involuntary contact with police only had indirect effects on citizens’ perceptions of police misconduct. Procedural justice was the most robust variable in predicting citizens’ perceptions of police misconduct.